Os acordos de pesca e as pescarias do Mapará (Hypophthalmus spp) em Limoeiro do Ajurú, nordeste do Estado do Pará - FERREIRA, Bruno Pantoja (2022)
Fishing is one of the main sources of income and food in the municipality of Limoeiro do Ajuru. The municipality has a very rich diversity of fish species, among them the mapará stand out. The importance of this fish is such that at the beginning of the fishing period, the “Borqueio do mapará” is held, which marks the end of the closed season, which runs from March to October. The borqueio is carried out by dozens of fishermen, which gives even more prominence to this action, which is considered a Cultural and Intangible event in the state of Pará. Despite so much wealth, in recent years, artisanal fishing in the municipality has shown a sharp drop motivated by the fall in production, a fact reported by fishermen in the region. Thus, this study aims to characterize the mapará fishery developed by artisanal fishermen from Limoeiro do Ajuru, taking into account the preservation during the closed season, the analysis of community fishing agreements and the monitoring of the capture and commercialization of this species, in order to guarantee strengthening the production chain and maintaining stocks, especially for those directly dependent on fishing activities. Analyzing the fisheries agreements that are outdated and without legal certainty, as they are not regulated.